1997
DOI: 10.1039/a607675k
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of radiation grafted and sulfonated poly(vinylidene fluoride), PVDF, membranes

Abstract: Radiation grafted and sulfonated poly(vinylidene fluoride), PVDF, membranes have been studied by thermal analysis and X-ray diÂraction to determine the changes in membrane crystallinity and structure during preparation. Commercial PVDF films were irradiated with an electron beam, grafted with styrene and finally sulfonated. Both the crystallinity and the size of the crystallites of PVDF decrease in the grafting reaction. A further decrease in crystallinity is observed in the sulfonation reaction. The residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 13 publications
7
87
1
Order By: Relevance
“…Because of incompatibility of polystyrene and PVDF, the grafts form phase separated regions, which are further reorganized in the following sulfonation reaction. 15,16 To further study the influence of crosslinking on the structure of the membranes, their crystallinity was determined. The inherent crystallinity of the PVDF decreases in the grafting process in the absence of crosslinkers and decreases further during the sulfonation.…”
Section: Crystallinitymentioning
confidence: 99%
See 2 more Smart Citations
“…Because of incompatibility of polystyrene and PVDF, the grafts form phase separated regions, which are further reorganized in the following sulfonation reaction. 15,16 To further study the influence of crosslinking on the structure of the membranes, their crystallinity was determined. The inherent crystallinity of the PVDF decreases in the grafting process in the absence of crosslinkers and decreases further during the sulfonation.…”
Section: Crystallinitymentioning
confidence: 99%
“…The inherent crystallinity of the PVDF decreases in the grafting process in the absence of crosslinkers and decreases further during the sulfonation. 16 The crystallinity of the crosslinked membranes was evaluated from results of thermal analysis differential scanning calorimetry, (DSC), and from wide-angle X-ray diffraction measurements (WAXS). In the thermal analysis the crystallinity was calculated from the enthalpies of fusion.…”
Section: Crystallinitymentioning
confidence: 99%
See 1 more Smart Citation
“…153 Poly(vinylidene fluoride)-(PVDF) based polymer membranes have also been prepared by grafting and then sulfonating the styrene groups, mainly by Sundholm's group. [154][155][156][157][158][159][160][161][162] The combination of the good physical stability and chemical resistance of PVDF with the good conductive properties of sulfonated polystyrene seems to give high water uptake 158 and high proton conductivity. [155][156][157] Partially fluorinated polymer membranes based on R, , -trifluorostyrenes have been prepared by either sulfonation 163 or phosphonation.…”
Section: Alternative Sulfonated Polymer Membranes and Their Compositesmentioning
confidence: 99%
“…This is due to dilution of the crystal line fraction by the incorporation of the amorphous PAAc chains into the polymer matrix. It can be concluded that the graft polymerization took place predominantly on the polymer film surface of the crystallites progressed inward thus breaking up partly ordered chain structures of the NWPP matrix [21].…”
Section: X-ray Diffraction Analysis (Xrd)mentioning
confidence: 99%